2021
DOI: 10.56093/ijans.v90i8.109298
|View full text |Cite
|
Sign up to set email alerts
|

Effect of replacing groundnut cake with dried Moringa oleifera leaves on growth and nutrient utilization in crossbred (Hampshire × Ghungroo) grower pigs

Abstract: The objective of this study was to evaluate the effect of replacement of groundnut cake with dried Moringa (Moringa oleifera) leaves on growth and nutrient utilization in crossbred grower pigs. Eighteen crossbred (Hampshire × Ghungroo) grower pigs (about 2 months old, body wt. 12–14 kg) of either sex were divided into three groups of six each in a randomized block design. Three different diets were used for feeding of the animals. These were namely, T1 (standard grower ration without dried Moringa leaves), T2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Barman et al (2015) [7] conducted an experiment on piglets by feeding three types of experimental diets containing WH at the rate of 0, 5 and 10% by replacing maize and designated as T 1 , T 2 and T 3 groups, respectively. In that study they found that there was no difference in DM intake (kg/d) across the groups.…”
Section: Discussionmentioning
confidence: 99%
“…Barman et al (2015) [7] conducted an experiment on piglets by feeding three types of experimental diets containing WH at the rate of 0, 5 and 10% by replacing maize and designated as T 1 , T 2 and T 3 groups, respectively. In that study they found that there was no difference in DM intake (kg/d) across the groups.…”
Section: Discussionmentioning
confidence: 99%